1984
DOI: 10.1161/01.hyp.6.5.743
|View full text |Cite
|
Sign up to set email alerts
|

Renal and systemic hemodynamics in sustained essential hypertension.

Abstract: SUMMARY Cardiac output (CO), renal blood flow (RBF), calf blood flow (CBF), and hepatic blood flow (HBF), glomerular filtration rate (GFR), and dopamine beta hydroxylase (D/3H) activity were studied in 198 men (67 normotensive controls and 131 hypertensive patients) of the same age with sustained uncomplicated essential hypertension. In the hypertensive men, the RBF and the RBF/CO ratio were significantly decreased (p < 0.001). The RBF and RBF/CO ratio were negatively correlated with age (p < 0.01), blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…3,4 Because RBF and cardiac output (CO) are strongly correlated, the ratio of both is a reliable parameter for the assessment of renal perfusion. 24,25 In this study, CO was not measured. However, potential confounding factors such as blood pressure or the size and structure of the heart, which reflect profound alterations in systemic hemodynamics, were similar between the different genotypes in our study population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…3,4 Because RBF and cardiac output (CO) are strongly correlated, the ratio of both is a reliable parameter for the assessment of renal perfusion. 24,25 In this study, CO was not measured. However, potential confounding factors such as blood pressure or the size and structure of the heart, which reflect profound alterations in systemic hemodynamics, were similar between the different genotypes in our study population.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported normal to enhanced renal blood and/or plasma flow in the prehypertensive stage and in borderline hypertension, 2,4,19 -22 whereas in sustained hypertension, the consistently observed pattern of renal hemodynamics is characterized by a decreased renal blood and/or plasma flow and a normal to slightly decreased GFR, resulting in an elevated renal filtration fraction. [23][24][25] Renal hemodynamic changes have been supposed to play an important role in the development of hypertension. Evidence for this hypothesis comes from the observation of an abnormal control of renal circulation in subjects with a positive family history of hypertension in response to mental stress, and Bianchi et al 4 found that normotensive offspring of hypertensive parents were characterized by high renal blood flow (RBF) despite normal cardiac output, suggesting a specific renal vasodilation in the prehypertensive stage.…”
Section: Discussionmentioning
confidence: 99%
“…5 Indeed, this increased resistance to blood flow is distributed throughout all tissues, 6 and Pickering observed that the so-called "minimum vascular resistance" (the resistance to blood flow after maximal vasodilation) remained increased in hypertensive patients. 7 Furthermore, Doyle and Black 8 showed that hypertension is associated with an increased "reactivity" of the forearm, i.e., infusion of agonists caused greater pressor responses in forearms of essential hypertensive patients.…”
Section: Essential Hypertensionmentioning
confidence: 99%
“…- 40 The decrease in renal blood flow and the renal fraction of cardiac output with hypertension was found to be reversible with administration of centrally acting sympatholytic agents. 26 - 28 However, structural processes in the renal vascular bed also appeared to be responsible for the age-related fall in renal perfusion, because age per se reduced the vasodilator response to administration of acetylcholine and sodium load. 41 Furthermore, a close negative relation between renal blood flow and the severity of arteriolar nephrosclerosis was noted in a series of more than 100 renal biopsies.…”
mentioning
confidence: 99%